PEMBERDAYAAN SANTRI PESANTREN BERWAWASAN KEAHLIAN, KETERAMPILAN, DAN KEMAMPUAN SOFT SKILL DI PROVINSI BENGKULU - Basuki Sigit Priyono; Eko Sumartono; Apri Andani; Ferzha Putra Utama (DHARMA RAFLESIA, 2018)
Pesantren, one of the containers and education community, is still considered less promising quality of general education for example in the form of appropriate technology and information technology. Technology misuse can indeed endanger the development of students, but if gives direction and carefully supervised by educators, of course technological developments can provide a soft skill that can be used by students after completing education from pesantren. Students in pesantren have a potential to be given material about the introduction of technology in various sciences and basic computer applications. The aim is the students are not surprised by the demands of post-pesantren technology as has been done by providing training on basic computer applications and the use of e-libraries. In addition, appropriate technology in the field of agriculture and fisheries is also transmitted to students to create a fish pond combined with aquaponic vegetation, such as vegetables. KKN program has provided many benefits related to learning and community empowerment. University of Bengkulu (UNIB),the nearest state university of pesantren, implement this KKN-PPM program through students from various disciplines and has been totally implemented in three pesantren and Bengkulu, such as Al-Hasanah, Hidayatullah, and Pancasila.Keywords: students, appropriate technology, pesantren, softskill